Antología del cuento chicano - Aguilar, Ricardo (1992)
Contiene cuentos de: Alice Gaspar, Alfonso Rodríguez, Justo S. Alarcón, Gloria Velásquez, Fausto Avendaño, Ricardo Aguilar, Daniel Venegas, Alurista, Sabine R. Ulibarrí, Tomás Rivera, Jim Sagel, José Antonio Burciaga, Miguel Méndez, Mendoza, Francisco Javier Alarcón, Sergio D. Elizondo y Ana María Salazar.